MSMES SECTOR IN INDIA: CURRENT STATUS AND PROSPECT (International Journal of Food and Nutritional Sciences, 2022)
Micro, Small, and Medium-Sized Enterprises (MSME) represent the backbone of an economy by fostering a discernible growth rate and creating employment opportunities. In many emerging and established economies, this sector has been viewed as a tool for socioeconomic growth. It generates a sizable entrepreneurial base in addition to making a substantial contribution to India's industrial production, export, and employment. The pandemic affects MSMEs adversely on a worldwide scale, and following COVID-19, the industry takes centre stage in powering the growth engine. The definition of MSMEs, their function and effectiveness in the current situation, as well as the sector's challenges and opportunities, are all examined in this essay. The study came to the conclusion that the pandemic has a negative impact on MSMEs and that the government needs to take appropriate action to mitigate this damage. Over the past fifty years, the Micro, Small, and Medium-Sized Enterprises (MSME) sector has grown to be a very active and dynamic area of the Indian economy. MSMEs not only play a significant role in creating many job opportunities at capital costs that are comparably lower than those of large industries, but they also aid in the industrialization of rural and underdeveloped areas, thereby reducing regional imbalances and ensuring a more equitable distribution of income and wealth across the country. MSMEs serve as auxiliary units to large businesses and have a significant positive impact on the nation's socioeconomic development. The Government of India has taken a number of initiatives to develop the sector in recognition of the sector's significant contribution to economic growth and the creation of jobs in our nation. For example, the definition of "Small Scale Industries" was expanded by raising the investment ceiling in plants and machinery from Rupees. The Micro, Small & Medium Enterprises Development (MSMED) Act, which went into effect on October 2, 2006, expanded the definition of MSMEs to include one crore of commercial activity. The MSME sector is a fantastic way to create inclusive and distributed growth as it is the second-largest employer in our nation.